Gastric Marginal Zone B Cell Lymphoma of the Duodenum - Ndzengue, A. (S. Karger AG, 2011)
Small bowel lymphomas of the extranodal type occur in the young and are characteristically associated with malabsorption syndrome. We present the case of an elderly in whom there was no malabsorption and the duodenal tumor was a gastric type marginal zone B cell lymphoma also known as gastric mucosa-associated lymphoid tissue (MALT) lymphoma. A 73-year-old woman presented to the emergency room with 2 weeks of general weakness, recurrent vomiting containing food particles and abdominal distension. She had been diagnosed with diabetic gastroparesis 4 years prior. CT of the abdomen and pelvis was suggestive of gastric outlet obstruction but no evidence of pancreatic or duodenal mass. Endoscopy and biopsy of the tumor obstructing the distal first part of the duodenum confirmed a gastric marginal MALT lymphoma. The patient's symptoms improved with radiotherapy. Gastric MALT lymphoma, an extranodal lymphoma primarily described in the stomach, can also present in the small bowel and is not associated with malabsorption.